2017
DOI: 10.1007/s00429-017-1547-3
|View full text |Cite
|
Sign up to set email alerts
|

Mapping GPR88-Venus illuminates a novel role for GPR88 in sensory processing

Abstract: GPR88 is an orphan G-protein coupled receptor originally characterized as a striatal-enriched transcript and is a potential target for neuropsychiatric disorders. At present, gene knockout studies in the mouse have essentially focused on striatal-related functions and a comprehensive knowledge of GPR88 protein distribution and function in the brain is still lacking. Here, we first created Gpr88-Venus knock-in mice expressing a functional fluorescent receptor to fine-map GPR88 localization in the brain. The rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 84 publications
(159 reference statements)
4
43
0
Order By: Relevance
“…This is consistent with the prominent expression of GPR88 in both striatum and cortex . This conclusion also fully accords our recent discovery of specific GPR88 expression in layer 4 of the somatosensory cortex, paralleling delayed sensory processing in Gpr88 −/− mice, as well as our recent fMRI data from Gpr88 −/− mice indicating disrupted functional connectivity predominantly at the level motor and sensory cortices, as well as the striatum in live mutant mice . In further support of our interpretation, the ventral striatum was shown activated in response to ingestive behavior, and dopamine levels in lateral hypothalamic area and the nucleus accumbens are associated with anticipatory and consummatory phases of feeding .…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with the prominent expression of GPR88 in both striatum and cortex . This conclusion also fully accords our recent discovery of specific GPR88 expression in layer 4 of the somatosensory cortex, paralleling delayed sensory processing in Gpr88 −/− mice, as well as our recent fMRI data from Gpr88 −/− mice indicating disrupted functional connectivity predominantly at the level motor and sensory cortices, as well as the striatum in live mutant mice . In further support of our interpretation, the ventral striatum was shown activated in response to ingestive behavior, and dopamine levels in lateral hypothalamic area and the nucleus accumbens are associated with anticipatory and consummatory phases of feeding .…”
Section: Discussionsupporting
confidence: 92%
“…11,12 GPR88 has also been found in other regions of the brain, including the cerebral cortex, amygdala, and hypothalamus. 1317 In the striatum, GPR88 is expressed at postsynaptic sites in medium spiny neurons (MSNs) of both direct and indirect pathways. 15 A number of studies using GPR88 knockout (KO) mice have suggested that genetic ablation of GPR88 induces a state of hypersensitivity to the dopamine system, and the receptor is implicated in disease states such as schizophrenia and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, cilia in midbrain dopaminergic and NAc GABAergic neurons express different complements of neuromodulatory receptors. For example, both MCHR1 and GPR88 are enriched in cilia in NAc, but are not detected in cilia on midbrain dopaminergic neurons [16,17,25] The results show that cilia ablation on either GAD2-GABAergic or dopaminergic neurons attenuates the locomotor stimulant effect of acute amphetamine. In contrast, cilia ablation on GAD2-GABAergic neurons enhances sensitization of the locomotor stimulant effect of repeated amphetamine, whereas ablation on dopaminergic neurons has no effect.…”
Section: Introductionmentioning
confidence: 81%
“…Across organ systems, cilia play a variety of signaling roles, largely related to sensing extracellular cues. Consistent with these roles, neuronal cilia express a variety of G protein-coupled receptors (GPCRs), several of which are rarely expressed outside of cilia [16][17][18]. Importantly, several of these GPCRs modulate behaviors related to drugs of abuse.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation